2017
DOI: 10.7287/peerj.preprints.3471v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical stratification of plant-pollinator interactions in a temperate grassland

Abstract: 11Visitation of plants by different pollinators depends on individual plant traits, spatial context, and other factors. A neglected aspect of small-scale variation of plant-pollinator interactions is the role of vertical position of flowers. We conducted a series of experiments to study vertical stratification of plant-pollinator interactions in a dry grassland. We observed flower visitors on cut inflorescences of Centaurea scabiosa and Inula salicina placed at different heights above ground in two types of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Indeed, their generalist behaviour, at the species level, could be the result of individually specialized diets, since most pollen retrieved on hoverfly individuals usually comes from a single plant taxon (Lucas et al ) and depends on flower availability and phenology (Cowgill et al , Colley and Luna , Lucas et al ). Moreover, some hoverflies have preferences regarding plant colour, morphology and inflorescence height (Branquart and Hemptinne , Colley and Luna , Lunau , Klecka et al , b).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, their generalist behaviour, at the species level, could be the result of individually specialized diets, since most pollen retrieved on hoverfly individuals usually comes from a single plant taxon (Lucas et al ) and depends on flower availability and phenology (Cowgill et al , Colley and Luna , Lucas et al ). Moreover, some hoverflies have preferences regarding plant colour, morphology and inflorescence height (Branquart and Hemptinne , Colley and Luna , Lunau , Klecka et al , b).…”
Section: Introductionmentioning
confidence: 99%
“…This may be partly caused by identical seed mix used for sown flower strips at all sites. How-ever, the beta-diversity of pollinators may be affected also be affected by phenology (Carvell et al 2006, Ouvrard et al, 2018) and heterogeneity of vegetation structure because pollinators tend to modify their preferences for flowers based on the characteristics of vegetation such as the composition of surrounding flowers (Janovský et al 2013) or the height of the surrounding vegetation (Klečka et al 2018a). Despite variable mowing regimes, such structural patterns of the vegetation were still more variable in semi-natural habitats than in sown flower strips.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the floral diversity of the sown flower strips would likely lead to an increase of the diversity of solitary bees (Wood et al 2017) and other pollinators. Most pollinators display preferences for various floral traits, such as flower size, colour, and shape (Junker et al 2013, Klečka et al 2018b), or vegetation structure, such as plant height (Klečka et al 2018a) and spatial clustering (Janovský et al 2013, Blaauw & Isaacs 2014, Akter et al 2017). Increasing the functional diversity of plants in the sown flower strips and their microhabitat heterogeneity might have beneficial effects on pollinator communities by providing suitable conditions for a broader range of species and by decreasing their competition with dominant species such as Apis mellifera (Forup & Memmott 2005, Hudewenz & Klein 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Flower number, plant height and flower size are also likely to be correlated with the overall resource status of individual plants (Hodgins & Barrett, 2008; Weiner, 1988). Many studies have demonstrated that fruit and seed production could increase with increasing flower number, plant height or mean flower size of individual plants (Andersson, 1991; de Jong, Waser, Price, & Ring, 1992; Klecka, Hadrava, & Koloušková, 2018; Mitchell, 1994; Ohara & Higashi, 1994; Ruane, Rotzin, & Congleton, 2014).…”
Section: Introductionmentioning
confidence: 99%